Industrialization, growth and the labour surplus model : the historical experience of Jamaica, and Trinidad and Tobago - Joefield-Napier, W. (1977)
Provides a summary description of the Lewis model and the major hypotheses that underlie it. Reviews the progress of economic development in Jamaica, and Trinidad and Tobago over the period 1950 through 1970, in the light of Lewis requirements for the transformation of dual economies. Seeks to shed light on the apparent failure of industrialization to solve the unemployment problem.